2001
DOI: 10.1086/322419
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Spectroscopy of II Pegasi: Coronal Temperature Structure, Abundances, and Variability

Abstract: We have obtained high-resolution X-ray spectra of the coronally active binary II Pegasi (HD 224085), covering the wavelength range of 1.5È25For the Ðrst half of our 44 ks observation, the source was in Ó. a quiescent state with constant X-ray Ñux, after which it Ñared, reaching twice the quiescent Ñux in 12 ks, then decreased. We analyze the emission-line spectrum and continuum during quiescent and Ñaring states. The di †erential emission measure derived from lines Ñuxes shows a hot corona with a continuous di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
120
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 37 publications
(45 reference statements)
17
120
0
Order By: Relevance
“…For short times, the luminosity can be several times higher; the flare of OID 7 emitted about 10 35 ergs. This is a typical size for RS CVn binaries (e.g., Maggio et al 2000;Huenemoerder et al 2001), but there have been flares 2 orders of magnitude larger (Ottmann & Schmitt 1994;Kuerster & Schmitt 1996). Perhaps the flare we missed in X-rays was of such a magnitude, given the large X-ray to EUV enhancement ratio we see near orbit 2.4 (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…For short times, the luminosity can be several times higher; the flare of OID 7 emitted about 10 35 ergs. This is a typical size for RS CVn binaries (e.g., Maggio et al 2000;Huenemoerder et al 2001), but there have been flares 2 orders of magnitude larger (Ottmann & Schmitt 1994;Kuerster & Schmitt 1996). Perhaps the flare we missed in X-rays was of such a magnitude, given the large X-ray to EUV enhancement ratio we see near orbit 2.4 (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Phillips et al (1996Phillips et al ( , 1997 used SMM data to infer electron density and emitting path lengths for the 15.01 Å emission using photon escape probability techniques. More recent observations of the 15-17 Å lines in stellar spectra obtained with Chandra and XMM-Newton (Canizares et al 2000;Brinkman et al 2000;Huenemoerder et al 2001) also reveal discrepancies between observed and theoretical ratios involving these transitions.…”
Section: Optical Depths Of the Coronal Plasmamentioning
confidence: 94%
“…The abundance of aluminum is constrained by the resonance transition of the helium-like ion at 7.76 Å , which is a significant detection (4 in HEG and 7 in MEG) and suggests an enhanced aluminum abundance. We compared this region of the spectrum with other active binary spectra reported in the literature: Capella, HR 1099 (Ayres et al 2001), II Peg , and AR Lac (Huenemoerder, Canizares, & Tibbetts 2002), the last three having similar temperature distributions to 2 CrB, and thus the spectra should be comparable. There is no feature of moderate strength at 7.22 Å in any of these spectra.…”
Section: -(A)mentioning
confidence: 99%
See 2 more Smart Citations